Upaya Antisipasi Tindak Asusila Di Lingkungan Institusi Pendidikan Formal Menurut Pandangan Agama Hindu - Pratiwi, Ni Putu Nita (Jayapangus Press, 2022)
Immoral acts are an extreme phenomenon and are very common in society. Immoral acts are an extreme phenomenon and are very common in society. The targets of victims are no longer only adults, but on the contrary, where the perpetrators are adults to children and adolescents. Of course, it is very sad considering that the perpetrators themselves are educated people and even have broad religious insight. The presence of this study aims to maximize preventive efforts when anticipating immoral acts that occur in formal educational institutions. As a characteristic of qualitative research, the data collection that is processed in this study is devoted to using library techniques and document recording. The data that has been obtained is then analyzed through qualitative descriptive techniques. The results of the analysis indicate that cases of immoral acts that occur in the formal education environment are still in the high category, which dominantly occurs in universities and islamic boarding schools, while in terms of the perpetrators of immoral acts themselves are dominantly carried out by teachers and lecturers. The triggering factors for immoral acts were recorded, including; The triggering factors for immoral acts were recorded, including; connectedness factor, biological factors, morality factor, education level factor or understanding, economic factor, social media factor and family condition factor. There are efforts that can be made in tackling the incidence of immoral acts according to the view of Hinduism, including by implementing severe sanctions (Criminal Law, Hindu Law and Customary Law) and actively holding religious counseling or socialization regarding these legal sanctions in formal educational institutions through Hindu-based organizations such as Parisada Hinduism, and deploying Hindu religious instructors.